Microbial Oxidative Enzymes Biotechnological Applications - Gupta, Arti; Kumar, Pankaj (De Gruyter, 2024)
Microbial oxidative enzymes are in need of today and in the future also. Several microbial oxidative enzymes are being used by various sectors like food, agriculture, medicine, detergents, leather, paper, etc. Microbial oxidative enzymes are a natural product, hence, the application of these enzymes is eco-friendly. Oxidative enzymes from microbes like bacteria, and fungi will be helpful in numerous applications including plant-soil health management, and waste treatments. This book will be more informative as well as useful for related industries and end users and will be of great value to those interested in present-day research on oxidation-reduction enzymes. In the coming years, this book will be a game changer for the field of oxidative enzyme development and its applications